2018
DOI: 10.1177/1455072518765875
|View full text |Cite
|
Sign up to set email alerts
|

Gambling participation, gambling habits, gambling-related harm, and opinions on gambling advertising in Finland in 2016

Abstract: Background: This report is an overview of results from the 2016 Finnish Gambling Harms Survey covering the population and clinical perspectives. It summarises the main findings on gambling participation, gambling habits, gambling-related harm, and opinions on gambling advertising. Methods: The population sample (n ¼ 7186) was collected from three regions and the clinical sample (n ¼ 119) in a gambling help clinic. Results: Frequency of gambling in the population sample was characteristically once a week, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(129 citation statements)
references
References 28 publications
7
118
2
2
Order By: Relevance
“…Gambling Marketing Perceptions Perceptions of gambling marketing seem, overall, quite negative and are often worse for active gamblers than for the general population [33,36,40]. Children also report being influenced by gambling marketing, such as financial incentives to gamble and odds advertising [14,20,41], for instance misperceiving marketing about financial incentives to mean that gamblers could never lose [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambling Marketing Perceptions Perceptions of gambling marketing seem, overall, quite negative and are often worse for active gamblers than for the general population [33,36,40]. Children also report being influenced by gambling marketing, such as financial incentives to gamble and odds advertising [14,20,41], for instance misperceiving marketing about financial incentives to mean that gamblers could never lose [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The research we find in this area is currently culturally homogenous, with most work to date coming from Australia. One exception is a general population study from Finland, where 20% felt that they had been exposed to too much gambling advertising, and 15% felt that advertising had made them gamble more [33]. These numbers were elevated in a separate clinical sample of treatment-seeking gamblers, with 68% feeling that they had been exposed to too much advertising and 35% that advertising had made them gamble more [33].…”
Section: Gambling Marketing Perceptionsmentioning
confidence: 99%
“…Evidence of the prevention paradox was found by several other studies [19,33,34] , though it was also found that the highest severity harms were generally only found in the problem Health Inequality in Gambling -14 gambling groups, as defined by the PGSI. Skaal et al [35] found psychological distress was only associated with problem gambling and Lloyd et al [36] found that self-harm thoughts were associated with problem gambling.…”
Section: And the Victorian Responsible Gamblingmentioning
confidence: 82%
“…In these public places gambling advertisement is also ordinary. Over half of Finnish women stated that the most common place to gamble was in grocery stores or supermarkets (Salonen, Hellman, Latvala, & Castrén, 2018). This should be noted when thinking about prevention of gambling problems.…”
Section: Discussionmentioning
confidence: 99%